ZIF‐8 as an adsorbent of aqueous phase for Eu and Tb ions. (1st March 2017) - Dai, Xiao‐qi; Hang, Yun‐hai; Zhao, Xin; Sun, Chao; Ju, Li‐na; Gui, Xiao‐jiao; Sun, Shuang; Xu, Yan‐bo; Wang, Yuan‐rui; Li, Ya‐feng
Abstract : In the present work, the adsorption behaviours of zeolitic imidazolate framework (ZIF‐8) as the adsorbent to europium (Eu) and terbium (Tb) in aqueous phase have considerably been investigated. ZIF‐8 shows the excellent adsorption performance such as quickness (in several minutes), efficiency (∼14% saturated amount) and lower adsorption limit (tens of parts per billion). Specially, ZIF‐8 prefers to adsorb lanthanide ions of low concentration (40 ppm) under high pH value (>6). Fourier transform infrared spectroscopy and X‐ray diffraction of used ZIF‐8 display that the hydroxyls generated from the hydrolysis of ZIF‐8 are responsible for catching the Eu or Tb by the formation of zinc (Zn)–O–Eu or Zn–O–Tb.